2010
DOI: 10.1021/es1012142
|View full text |Cite
|
Sign up to set email alerts
|

Using Spectrophotometric Titrations To Characterize Humic Acid Reactivity at Environmental Concentrations

Abstract: Potentiometric titration is a common method to characterize dissolved organic matter (DOM) reactivity. Because of the sensitivity of pH electrodes, it is necessary to work with very high DOM (>1 g/L) concentrations that are unrealistic compared to those found in natural waters (0.1 to 100 mg/L). To obtain proton binding data for concentrations closer to environmental values, spectroscopic titration methodology is a viable alternative to traditional potentiometric titrations. Spectrophotometric titrations and U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 39 publications
4
81
0
1
Order By: Relevance
“…This was important to avoid changes in the pH-dependent shift in absorbance and photobleaching as described elsewhere (Pace et al, 2012;Janot et al, 2010). The samples were then divided and half of the sample (20 mL) was continuously pumped through a custom-built photo reactor cell made out of Tefzel tubing for 24 h. A 10 mL gas equilibrator was also attached in-line to allow saturation of air gases at any given time.…”
Section: Photochemical Experimentsmentioning
confidence: 99%
“…This was important to avoid changes in the pH-dependent shift in absorbance and photobleaching as described elsewhere (Pace et al, 2012;Janot et al, 2010). The samples were then divided and half of the sample (20 mL) was continuously pumped through a custom-built photo reactor cell made out of Tefzel tubing for 24 h. A 10 mL gas equilibrator was also attached in-line to allow saturation of air gases at any given time.…”
Section: Photochemical Experimentsmentioning
confidence: 99%
“…5. This model may appear too simplistic, but (i) the amount of the different fractions was not sufficient to perform reliable acid-base titrations [30], and (ii) the application of generic parameters, as those selected otherwise [28,29,61], may not be directly applied to our case. As by our approach, the magnitude of logˇ(complexation strength) was not the most influencing parameter, while it was instead the number of available complexation sites that explained most of modifications in GHA separated fractions.…”
Section: Comparisons Of the Complexometric Titrationsmentioning
confidence: 99%
“…Christl et al showed that the functionality [28] and metal binding [29] of different size-fractions of a HA from ultrafiltration were comparable within a narrow range. Conversely, Hur and Schlautman [25], Reiller et al [27] and Janot et al [30] showed that clear modification occurred on mass-distribution and acid-base properties of HA after sorptive fractionation. In addition, Claret et al [26] noted that the influence of sorptive fractionation of HS on ␣-Al 2 O 3 was important from the evolution of the chemical environment of europium(III) by time-resolved luminescence spectroscopy (TRLS).…”
Section: Introductionmentioning
confidence: 98%
“…The absorbance of DOM is also sensitive to DOM interactions with the proton and metal cations (Dryer et al, 2008;Janot et al, 2010;Yan et al, 2013a;Yan and Korshin, 2014). In absorbance measurements, the concept of differential absorbance allows ascertaining the general types of the involved functional groups and extent of their interactions with protons and metal cations.…”
Section: Introductionmentioning
confidence: 99%